Centrica : strategizing in a multi-utility - Paroutis, Sotirios (London : SAGE Publications Ltd, 2016)
The case describes how Sir Roy Gardner became CEO of Centrica after its demerger from British Gas and turned the failing company around for it eventually to become a success. Roy Gardner replaced the old utility model they had inherited from British Gas and instead developed a business model where customer satisfaction and retention would be central.
Originally published in Paroutis, S. (2016). Centrica: Strategizing in a multi-utility. In S. Paroutis, L. Heracleous, & D. Angwin (Ed.), Practicing strategy: Texts and cases (2nd ed., pp. 191-211). London, UK: SAGE Publications Ltd. ISBN: 9781473912854.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gardner, Roy, -- Sir; Centrica plc; Gas industry -- Great Britain; Success in business; Industrial management